Effects of phase shift on the heat transfer characteristics in pulsating mixed convection flow in a multiple vented cavity - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Science Inc, 2015)
In the current study, numerical investigation of pulsating mixed convection in a multiple vented cavity with phase shift is carried out for the range of parameters; Richardson number (0.25 <= Ri <= 4), phase shift (0 <= phi <= pi) and Strouhal number is fixed at 1. The governing equations are solved with a general purpose finite volume based solver. The effects of Ri number and phase shift parameters on the fluid flow and heat transfer characteristics are numerically studied. It is observed that the flow field and heat transfer enhancement are influenced by the variation of these parameters. Furthermore, recurrence plot analysis is applied for the analysis of the time series (spatial averaged Nusselt number along the vertical wall of the cavity) and for a combination of different parameters, the systems are identified using recurrence quantification analysis parameters including recurrence rate, laminarity, determinism, trapping time and entropy. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Mixed convection; Phase shift; Recurrence quantification analysis; Pulsating flow